An Analysis of Competition among Autonomous Devices in Multichannel Cognitive Radio Networks - DA SILVA, LUIZ (My University, 2012)
We investigate an autonomous opportunistic spec- trum access (OSA) strategy for a multichannel cognitive radio (CR) network, where two or more autonomous CRs sense the channels sequentially in some sensing order to find a free channel to transmit on, if one exists. We evaluate the performance of the OSA strategy in terms of probability of success (probability that a given CR finds a channel free), mean time of success and throughput achievable by a CR. Surprisingly, we find that, when the number of potentially available channels is not large as compared to the number of CRs in the network, then having more free channels beyond a certain number actually hurts the CRs. This counter-intuitive result stems from an increased number of collisions among the autonomous CRs. To validate the closed form expressions that are derived in this paper, we compare our results to those obtained via simulations.
7th Intl. Conf. on Cognitive Radio Oriented Wireless Networks (CROWNCOM)
PUBLISHED
Stockholm, Sweden
Keywords: Wireless Networks; Telecommunications